An integrated data analysis reveals distribution, hosts, and pathogen diversity of Haemaphysalis concinna - Jing Liu; Xiao-Yu Han; Run-Ze Ye; Qing Xu; Xiao-Yang Wang; Ze-Hui Li; Yi Sun; Ke Song; Bao-Yu Wang; Shan-Shan Wang; Jin-Yue Liu; Lin Zhao; et al. (Parasites & Vectors, 2024)
Abstract Background Haemaphysalis concinna, carrying multiple pathogens, has attracted increasing attention because of its expanded geographical range and significant role in disease transmission. This study aimed to identify the potential public health risks posed by H. concinna and H. concinna-associated pathogens. Methods A comprehensive database integrating a field survey, literature review, reference book, and relevant websites was developed. The geographical distribution of H. concinna and its associated pathogens was illustrated using ArcGIS. Meta-analysis was performed to estimate the prevalence of H. concinna-associated microbes. Phylogenetic and geographical methods were used to investigate the role of birds in the transmission of H. concinna-associated microbes. The potential global distribution of H. concinna was predicted by ecological niche modeling. Results Haemaphysalis concinna was distributed in 34 countries across the Eurasian continent, predominantly in China, Russia, and Central Europe. The tick species carried at least 40 human pathogens, including six species in the Anaplasmataceae family, five species of Babesia, four genospecies in the complex Borrelia burgdorferi sensu lato, ten species of spotted fever group rickettsiae, ten species of viruses, as well as Francisella, Coxiella, and other bacteria. Haemaphysalis concinna could parasitize 119 host species, with nearly half of them being birds, which played a crucial role in the long-distance transmission of tick-borne microbes. Our predictive modeling suggested that H. concinna could potentially survive in regions where the tick has never been previously recorded such as central North America, southern South America, southeast Oceania, and southern Africa. Conclusions Our study revealed the wide distribution, broad host range, and pathogen diversity of H. concinna. Authorities, healthcare professionals, and the entire community should address the growing threat of H. concinna and associated pathogens. Tick monitoring and control, pathogen identification, diagnostic tools, and continuous research should be enhanced. Graphical Abstract